Cryoconservation de matériel génétique de bananier: 2ème édition - Engelmann, F.; Benson, E.; Bioversity International (2009)
The aim of this publication is to provide information and guidance on cryopreservation methodologies suitable for use on Musa germplasm. The different methods currently used at Katholieke Universiteit Leuven (KULeuven) for cryopreserving Musa cultures are described as well as the advantages and disadvantages of each of them. The areas where research is still required to further optimize the protocols are also identified. It is hoped that the detailed descriptions of the methodologies will facilitate their adoption and standard use in different laboratories